Characteristics and Research Direction of Triassic in the South Yellow Sea Basin, China. (17th March 2022) - Weijun, Kong; Shuzhen, Su; Jianning, Zhang; Guoji, Shi; Yao, Huang; Kui, Zhu; Qinghua, Chen
Abstract : To advance oil and gas exploration in the South Yellow Sea Basin, characteristics of Triassic, including its correlation with regional strata, distribution, lithology characteristics, and karst development characteristics, are studied by geological mapping. Results show that there exist Zhouchongcun Formation and Qinglong Formation in the Triassic. Zhouchongcun Formation corresponds to Dongma Formation in the lower Yangtze Region, Badong Formation in the middle Yangtze Region, and Lekoupo Formation in the upper Yangtze region. The upper Qinglong Formation corresponds to the Nanlinghu Formation and Longshan Formation in Xiyanzi district, and Jialingjiang Formation in the middle and upper Yangtze region. Its lithology is limestone, intercalated with marl, mudstone, and argillaceous siltstone. The lower Qinglong Formation corresponds to the Yinkeng Formation at the lower Yangtze group. The lower Qinglong group has the complex lithologic characteristics, which can be divided into six categories from top to bottom, including limestone weathering crust layer, limestone, marl with mudstone, mudstone with limestone, marl with limestone, and mudstone interbedding limestone and mudstone. Karst phenomenon is well developed in the lower Qinglong Formation, and the thickness of weathering crust, revealed by cz35-2-1 well, reaches 60.5 m. Triassic in the South Yellow Sea Basin is mainly distributed in the central uplift and southern depression, showing the regional differences in distribution. Karstification is probably the main reason for this significant difference. Identification of karst phenomenon and stratigraphic division method towards Triassic drilling coring are two important directions of Triassic study in the South Yellow Sea Basin.